Toxicities in long-term survivors of head and neck cancer: a multi-national cross-sectional analysis - Taylor, Katherine Joyce; Amdal, Cecilie D.; Bjordal, Kristin; Astrup, Guro L.; Herlofson, Bente B.; Duprez, Fréderic; Gama, Ricardo R.; Jacinto, Alexandre; Hammerlid, Eva; Scricciolo, Melissa; Jansen, Femke; Verdonck-de Leeuw, Irma M.; et al. (International journal of cancer, 2025)
Head and neck cancer (HNC) patients may experience toxicities as a result of their treatment modality. While acute toxicities have been well documented, the prevalence of toxicities at long-term follow-up of HNC survivors is less clear. As part of a multi-national, cross-sectional study, HNC survivors at least 5 years post-diagnosis were invited to undergo a toxicity examination. Using the Common Terminology Criteria for Adverse Events (version 5), 33 toxicities were assessed. From 2019 to 2021, 1094 survivors from 26 sites in 11 countries completed the assessment. Eighty-seven percent were from Europe, and most were survivors of oropharynx (35%), oral cavity (21%), or larynx cancer (19%). The majority had been diagnosed at stage III or IV (62%), and the median time since diagnosis was 8 years (range 5-36). Most had been treated with surgery and radiotherapy with or without chemotherapy (38%). Six percent had no toxicities, and 26% had only mild toxicities. 68% had at least one moderate or severe late toxicity. Overall, the most frequent late toxicities at any grade were dry mouth (67%), soft tissue fibrosis (52%), dysphagia (51%), and voice alterations (39%). Fistulae, neck and face edema, and osteonecrosis of the jaws were present in very few survivors. Our study shows that the majority of HNC survivors experience moderate or severe late toxicities, but that the problems are concentrated in a small group of specific toxicities. Understanding the problems experienced in the long term can help better inform newly diagnosed patients as well as inform survivorship follow-up initiatives.
Gesehen am 12.01.2026